2019
DOI: 10.1371/journal.pone.0223611
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Trypanosoma cruzi infection in active military population of The Colombian National Army gathered in five departments

Abstract: BackgroundThe National Army of Colombia is present in all of the national territory, focused in sylvatic zones where they are exposed continually to potential risk of transmission of Trypanosoma cruzi, the etiological agent of the Chagas disease. People of this study were active personal that were born and lived during their first years in endemic areas of transmission through domiciled vectors as Rhodnius prolixus.AimThe main aim of this study was to estimate the prevalence of Chagas disease in the active mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The soldiers actively protect Colombia’s sovereignty in border areas and patrol and maintain public order in all municipalities, including those with enzootic transmission of T. cruzi . Acute cases of CD related to vectorial and oral transmission as well as chronic cases among active military personnel in military installations are usually reported in the National Public Health Surveillance System (SIVIGILA) [ 33 – 35 ]. A recent study of T. cruzi infection among the active military population found that around 70.5% of the evaluated population were born in municipalities that have reported infected triatomines [ 35 37 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The soldiers actively protect Colombia’s sovereignty in border areas and patrol and maintain public order in all municipalities, including those with enzootic transmission of T. cruzi . Acute cases of CD related to vectorial and oral transmission as well as chronic cases among active military personnel in military installations are usually reported in the National Public Health Surveillance System (SIVIGILA) [ 33 – 35 ]. A recent study of T. cruzi infection among the active military population found that around 70.5% of the evaluated population were born in municipalities that have reported infected triatomines [ 35 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acute cases of CD related to vectorial and oral transmission as well as chronic cases among active military personnel in military installations are usually reported in the National Public Health Surveillance System (SIVIGILA) [ 33 – 35 ]. A recent study of T. cruzi infection among the active military population found that around 70.5% of the evaluated population were born in municipalities that have reported infected triatomines [ 35 37 ]. In this context, it is possible that military personnel exposed to different scenarios of CD transmission could converge in battalions or cantonment centers, combined with the existence of triatomines bugs and reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…One limitation of this report is the lack of confirmation of the source of the outbreak. In previous studies in Colombia, evidence of T. cruzi seropositivity was demonstrated in 1% of the military population studied in 5 departments ( 3 ), but no similar studies have been conducted in the area where the outbreak cases in this study originated. Despite the reported low vector contact among military personnel, the geographic characteristics of the region where this outbreak originated are similar to areas with higher vector populations, raising the possibility of sylvatic zoonotic oral transmission.…”
Section: Discussionmentioning
confidence: 48%
“…However, acute forms account for ≈1% of reported cases and can have severe clinical manifestations, especially when orally acquired because of the particularly high parasitic load from this transmission route ( 1 ). Some populations can be at high risk for infection, including military personnel who are in endemic areas patrolling in rural or jungle environments where the parasite has been documented in multiple reservoirs ( 2 , 3 ). Although vectorborne transmission is most common, oral transmission has been associated with outbreaks of acute Chagas disease in Latin America and has case fatality rates of 8%–35% ( 1 ).…”
mentioning
confidence: 99%
“…Chagas disease has been detected worldwide although vector transmission is limited to Latin America, where it also shows the highest prevalence ( Méndez et al, 2019 ; Olivera et al, 2019 ; Serra et al, 2019 ; Lidani et al, 2019 ). Bolivia is the country with the highest prevalence and incidence of the disease: more than 600,000 people are infected with an annual average of 8000 new infections ( World Health Organization, 2015 ).…”
Section: Introductionmentioning
confidence: 99%